Las universidades ecuatorianas y su aporte en la innovación social a través del desarrollo de investigaciones participativas (Tema Central) - Orellana Navarrete, Ana Verónica (2024)
This article brings light to one of the phases of doctorate-level investigation on the role of the universities in Ecuador for the social innovation process. The objective is to identify investigation projects performed with participation of Ecuadorian universities from the approach of social management with several actors involved. A systematic literature- based mapping was used to choose and analyze 33 publications to identify investigation performed with participative methodologies such as co-design, co-production or investigation-action. The databases WoS and Scopus were used, with results showing that there is a limited number of investigation applying co-design, no investigations with co-production, and most of the articles studies report to have used investigation-action. Several projects that imply participation of the community related to the issue were presented in most cases. This mapping presented 12 projects that align with the social innovation process, applying methods and techniques that promote actor participation, which also supports the understanding of how universities may fulfill their substantive function of performing research while responding to contextualized social needs.